Teorias da decisão, direito tributário e sustentabilidade - Tomkowski, Fábio Goulart (2015)
In this work will be analyzed the main decision theories, approaching their main features and the arguments in favor and against them. Will be conducted, also, a critical approach about the Brazilian tax law system, specially its unsustainability, in order to, based on the knowledge about the decision theories, verify the tendencies in the human behavior that affects the formulation of the public policies and in its efficiency. Then, will be seek to establish some guidelines, taking into account the decision theories, especially the Behavioral Law and Economics, in order to contribute to make the public policies, mainly the tax policies, more sustainable and in accordance with the rights and guarantees expressed in the Brazilian Constitution.